2021
DOI: 10.1111/jocd.14119
|View full text |Cite
|
Sign up to set email alerts
|

Health knowledge and motives on tattooing: A community‐based cross‐sectional study in Greece

Abstract: Background: Tattooing is becoming an increasingly common trend mainly but not merely among the youth. However, the choice of ink body art is associated with an increase of dermatological complications. Aim:To assess young persons' health knowledge and motives toward tattooing. Methods:The main instrument used was an online structured questionnaire with scaling and dichotomous questions, consisting of three components: (a) the participants' sociodemographic profile, (b) health knowledge assessment, (c) motives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…[ 9 ] A survey from Greece demonstrated that 77% of all subjects had motives of ideology, message or fashion. [ 21 ] Tiggemann and Golder found that men had higher scores regarding tattoo motivations of ‘to show commitment to a group’. [ 8 ] Weiler et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] A survey from Greece demonstrated that 77% of all subjects had motives of ideology, message or fashion. [ 21 ] Tiggemann and Golder found that men had higher scores regarding tattoo motivations of ‘to show commitment to a group’. [ 8 ] Weiler et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some "collect" this art and choose to be tattooed by various artists to amass a collection of tattoos on their body, while for others, a tattoo is simply attained for the sake of fashion [39]. A survey from Greece demonstrated that 77% of all subjects had motives of ideology/message and fashion/esthetic [40]. Likewise, it was noted that personal and esthetic preferences were strong motivators, especially for transmasculine persons in a study [41].…”
Section: Emotions and Motivations In Tattooed Peoplementioning
confidence: 99%
“…However, this growing demand has increased the number of unprofessional body art practitioners performing procedures that require more adherence to safe and healthy hygienic standards [ 3 ]. Consequently, the frequency of recorded adverse health hazards after tattooing has increased [ 4 ]. The prevalence of cutaneous complications of tattoos ranges from 2%-43% [ 5 , 1 , 6 ], even though the cutaneous complications are higher than the systemic complications.…”
Section: Introductionmentioning
confidence: 99%